IRCTC'S SHARE PRICES ON THE NATIONAL STOCK EXCHANGE (NSE) ARE BEING EVALUATED WITH REFERENCE TO THE INDIAN LOCKDOWN. - Jain, Vipin (Journal of Advanced Research in Economics and Business Management, 2023)
The purpose of the paper is to analyse and assess the share price performance of IRCTC since its listing on the Indian NSE. The report also focuses on analysing the share price performance before and after the announcement of the lockdown in India. The research design is primarily descriptive. Data are gathered for the daily share prices of IRCTC on the NSE in India from October 14, 2019, to January 15, 2021. To analyse the pricing, descriptive statistics and one variable analysis were used. t test and Kolmogorov-Smirnov test were used to analyse the pre- and post-performance of pricing. IRCTC Share experienced significant appreciation at the time of listing on NSE because of its solid fundamentals. Additionally, the rally went on thanks to investors' upbeat attitudes. The Indian government declared a lockdown in response to the growing threat of a pandemic, which paralysed the whole country's rail system as well. According to the analysis, the IRCTC share prices began to decline one month before the country was put on lockdown, and they continued to do so up until the start of the lockdown. The IRCTC share price experienced a V-shaped rebound after the lockdown, and it was able to reclaim its position.